Parameter Pengawasan Pemerintah Terhadap Peraturan Daerah Yang Berciri Khas Daerah - Picauly, Benjamin Carel; Sedubun, Victor Juzuf (Postgraduate Program Doctoral in Law, Universitas Pattimura, 2022)
Introduction: Supervision of Regional Regulations according to the 1945 Constitution of the Republic of Indonesia, Law Number 23 of 2014, PP Number 79 of 2005 and Permendagri Number 1 of 2014 is carried out by the Government. In exercising the authority to supervise Regional Regulations, the Government is limited to the parameters regulated by laws and regulations. Purposes of the Research: To analyze the supervision Parameters of Regional Regulations regulated in Law Number 23 of 2014. Methods of the Research: This research is a normative research, with a statutory approach and a conceptual approach. Results Originality of the Research: The results of the research found that the provisions of Article 7 of Law Number 12 of 2011 are in accordance with the principle of lex superiori derogate legi inferiori, namely a regulation may also not apply if it clearly contradicts a higher regulatory norm. In a theoretical perspective, the principle of lex superiori derogate legi inferiori was developed by Hans Kelsen and Hans Nawiasky through tiered legal norms.